Comparative Efficacy of Three Forms of Parenteral Iron. (19th January 2012) - Dillon, Richard; Momoh, Ibrahim; Francis, Yvonne; Cameron, Laura; Harrison, Claire N.; Radia, Deepti
Abstract : Intravenous iron therapy is a useful treatment for the rapid correction of iron deficiency anaemia and can be used to avoid or reduce the requirement for allogeneic blood transfusion. Several intravenous iron preparations are available commercially which differ in cost, mode of administration and side effect profile. There are few data directly comparing the efficacy of these preparations. In this retrospective single-centre study, we present the results from two hundred and eight patients treated using three different iron preparations (iron dextran, iron sucrose and ferric carboxymaltose) and compare the effect on haemoglobin levels and other measures of iron deficiency six weeks after treatment. Within the limitations of our study design, we show a statistically and clinically significant difference in efficacy between these preparations.